A new approach to nuclear level densities: The QRPA plus boson expansion - S. Hilaire; S. Goriely; S. Péru; G. Gosselin (Physics Letters B, 2023)
Nuclear level densities play a key role in many nuclear applications. To go beyond the usual particle-independent approximation, a conceptually new approach based on the boson expansion of QRPA excitations is proposed. The calculated nuclear level densities are shown to follow an energy dependence close to a constant-temperature formula at energies above a few MeV, but present a rather narrow spin distribution. They are shown to provide a quite remarkable agreement with s-wave resonance spacings and Oslo data, at least for the 48 even-even nuclei considered in the present study.